1988
DOI: 10.1161/01.hyp.11.2_pt_2.i80
|View full text |Cite
|
Sign up to set email alerts
|

Implication of leumorphin in inhibitory control of vasopressin secretion in conscious rats.

Abstract: TAKAYUKI YAMADA, KAZUWA NAKAO, HIROSHI ITOH, NARITO MORII, SHOZO SHIONO, MAKOTO SAKAMOTO, AKIRA SUGAWARA, YOSHIHIKO SAITO, MASASHI MUKOYAMA, HIROSHI ARAI, AND HIROO IMURA SUMMARY The effects of leumorphin, a K-agonist derived from proenkephalin B (neoendorphin and dynorphin precursor), on vasopressin secretion were studied under basal and stimulated conditions in conscious, unrestrained rats. Intracerebroventricular injection of leumorphin (60 or 600 pmol) significantly inhibited basal vasopressin secretion. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Some studies demonstrated diureses or a decrease in vasopressin release by K-agonists injected into the ventri cle (14)(15)(16). This is not consistent with our present results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies demonstrated diureses or a decrease in vasopressin release by K-agonists injected into the ventri cle (14)(15)(16). This is not consistent with our present results.…”
Section: Discussionmentioning
confidence: 99%
“…These antidiuretic effects, at least in part, appear to be induced by increased vasopressin re lease, although there are some reports that the opioid agonists show decrease or have no effect on the firing rate of vasopressin-containing neurons or vasopressin release (4,(9)(10)(11)(12)(13). On the other hand, c-agonists injected into the ventricle decrease vasopressin release and induce diuretic effects (14)(15)(16). Systemic administered K-agonists also elic it the same effects, which are suggested to be mediated through K-receptors on the neurohypophysis (16)(17)(18)(19).…”
mentioning
confidence: 99%